2021
DOI: 10.1177/1362361321990928
|View full text |Cite
|
Sign up to set email alerts
|

Adults with autism spectrum disorder show atypical patterns of thoughts and feelings during rest

Abstract: Mind wandering constitutes a major part of everyday experience and is inherently related to how we feel and identify ourselves. Thus, probing the character and content of thoughts and feelings experienced during mind-wandering episodes could lead to a better understanding of the human mind in health and disease. How mind wandering and spontaneous thought processes are affected in disorders such as autism is poorly understood. Here, we used the eyes-closed rest condition to stimulate mind wandering and quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…One must feel comfortable to maintain focus of attention, including to own thoughts as reflected in the strong negative correlations between Discontinuity of Mind and Comfort (Diaz et al, 2013). Several studies using the ARSQ have reported reduced Comfort in clinical cohorts, including insomnia (Palagini et al, 2016), autism (Simpraga et al, 2021), and also health anxiety and obsessive compulsive disorder (Gehrt et al, 2020). Thus, there is a need and our results indicate a potential for MBSR to facilitate a greater feeling of comfort in these disorders.…”
Section: Does General Well-being Drive Our Thoughts and Feelings In Every Moment?mentioning
confidence: 70%
See 1 more Smart Citation
“…One must feel comfortable to maintain focus of attention, including to own thoughts as reflected in the strong negative correlations between Discontinuity of Mind and Comfort (Diaz et al, 2013). Several studies using the ARSQ have reported reduced Comfort in clinical cohorts, including insomnia (Palagini et al, 2016), autism (Simpraga et al, 2021), and also health anxiety and obsessive compulsive disorder (Gehrt et al, 2020). Thus, there is a need and our results indicate a potential for MBSR to facilitate a greater feeling of comfort in these disorders.…”
Section: Does General Well-being Drive Our Thoughts and Feelings In Every Moment?mentioning
confidence: 70%
“…Using the ARSQ, reproducible patterns of individual thoughts and feelings have been observed, and associated with scores on insomnia, anxiety, and depression in large population samples (Diaz et al, 2013). Likewise, mental disorders including health anxiety, obsessive compulsive disorder (Gehrt et al, 2020) insomnia disorder (Palagini et al, 2016) and autism spectrum disorder (Simpraga et al, 2021) have been associated with distinct ARSQ profiles. Studies of the therapeutic benefits of MBSR have used clinical scales that refer to experiences during weeks or even months to assess participants' well-being, as well as symptoms of stress, anxiety, and depression.…”
Section: Introductionmentioning
confidence: 96%
“…The ability to relax and feel comfortable is related to interoceptive aspects through the urge to restore balance in physical and emotional context [56,57]. The domain of Comfort was previously related with the ability to switch between tasks [58], correlated with character traits of self-directedness (associated with individual ability to govern behavior according to situational demand) [13] and mental and physical well-being [12].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Helfer et al, 47 MEWS scores did not differ between adults with ADHD and ASD, both of which were higher than those of the controls. Similar neural abnormalities associated with DMN and MW have been reported in ADHD and ASD 45,48–50 ; however, the mechanisms or content of MW may differ 47,51 . Given that individuals with both ADHD and ASD exhibit greater impairments in various domains than those with only ADHD, 52 elevated MW with an association with AQ scores may reflect the social impairments experienced by the participants.…”
Section: Discussionmentioning
confidence: 69%